The Emerging Mechanisms of Wnt Secretion and Signaling in Development - Mehta, Shefali; Hingole, Swapnil; Chaudhary, Varun (Frontiers in Cell and Developmental Biology, 2021)
Wnts are highly-conserved lipid-modified secreted proteins that activate multiple signaling pathways. These pathways regulate crucial processes during various stages of development and maintain tissue homeostasis in adults. One of the most fascinating aspects of Wnt protein is that despite being hydrophobic, they are known to travel several cell distances in the extracellular space. Research on Wnts in the past four decades has identified several factors and uncovered mechanisms regulating their expression, secretion, and mode of extracellular travel. More recently, analyses on the importance of Wnt protein gradients in the growth and patterning of developing tissues have recognized the complex interplay of signaling mechanisms that help in maintaining tissue homeostasis. This review aims to present an overview of the evidence for the various modes of Wnt protein secretion and signaling and discuss mechanisms providing precision and robustness to the developing tissues.